Kantorovich Type q-Bernstein Polynomials - Elatrash, Abubaker Banour Masoud (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2017)
In this thesis first of all some elementary results related with positive linear operators, properties of Bernstein operators, q-integers and some identities related with q-integers and also q-Bernstein operators and their properties are studied. Later a q-analogue of the Bernstein-Kantorovich operators, their approximation properties, local and global approximation properties and Voronovskaja type theorem for the q-Bernstein-Kantorovich operators for the case 0<q<1 are examined.

ÖZ: Bu tezde ilk önce pozitif lineer operatörler ve bu operatörlerin özellikleri, bu operatörlerle ilgili sonuçlar, Bernstein operatörleri incelenmiştir. Ayrıca tamsayıların q-analoğu ve bunlarla ilgili bazı özdeşlikler verildikten sonra Bernstein operatörlerinin q-analoğu ve özellikleri çalışılmıştır. Daha sonra Bernstein-Kantorovich operatörleri ve Bernstein-Kantorovich operatörlerinin q-analoğu verilip q-Bernstein-Kantorovich operatörlerinin yakınsaklık özellikleri, lokal ve global yakınsaklık özellikleri ve 0<q<1 için Voronovskaya tipi teorem incelenmiştir
Master of Science in Mathematics. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Arts and Sciences, Dept. of Mathematics, 2017. Supervisor: Assist. Prof. Dr. Pembe Sabancıgil.
Keywords: Mathematics; Bernstein polynomials; Kantorovich operators; q-type Kantorovich operators; q-Bernstein polynomials; local and global approximation